Multilevel relational influences on HRM practices: a cross-country comparative reflective review of HRM practices in Asia - Ashish Malik; Vijay Pereira; Pawan Budhwar; Fabian Jintae Froese; Dana Minbaeva; James Sun; Anh Tuan Nguyen; Shanzi Xue (Asian Business & Management, 2022)
In this paper, we respond to the calls for context-specific scholarship and research on human resource management (HRM) in Asia. We provide an overview of and key insights into HRM in five Asian countries, representing five key regions: China (East Asia), India (South Asia), Kazakhstan (Central Asia), United Arab Emirates (West Asia), and Vietnam (Southeast Asia). Based on our comprehensive, pan-Asian review, we develop a reflective, comparative, and relational understanding of HRM practices. In doing so, we group the myriad contextual influences on the shaping of HRM practices at three broad levels: macro-, meso-, and microlevel influences. Specifically, we propose that influences from regionalization of economies, national business systems, industry, multinational enterprises, and individual-level predispositions collectively shape and variously influence the nature and extent of HRM practices. By considering the findings of prior research on convergence and divergence, we offer a nuanced perspective wherein each country and region in Asia possesses a distinct amalgam of national business systems, and where HRM practices respond to multilevel influences in varied ways.
Keywords: 650; HRM practices; Cross-country comparative review; Asia; Convergence; Divergence